Analisis Profil Pelajar Pancasila Dalam Proses Pembelajaran Biologi SMA Pada Kurikulum Merdeka Mandiri Belajar: (Analysis of Pancasila Student Profiles in the Biology Learning Process at Senior High School in the Merdeka Curriculum Category Independent Study) - Amarina At'haya; Anna Fitri Hindriana Anna Fitri Hindriana; Sofyan Hasanuddin Nur Sofyan Hasanuddin Nur (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
The purpose of this study is to analyze the profile of Pancasila in biology learning. This research is a descriptive qualitative research, with a research sample of six high schools implementing the Merdeka Curriculum in the independent learning category. taken proportionally between public and private schools. The informants of this study were grade X Biology teachers. Data collection was carried out using questionnaires, interviews, and documentation. Qualitative data analysis is carried out with data reduction, data display, and conclusion drawing activities. The results showed that the implementation of strengthening the Pancasila learner profile in the biology learning process has been carried out by finding the values of the Pancasila learner profile dimensions, namely the dimensions of critical reasoning, noble character, mutual cooperation, and creativity. The value of the critical reasoning dimension is the most dominant. However, there are still shortcomings in its implementation related to the fact that teachers have not fully adapted learning to the conditions of students and conducted diagnostic assessments for differentiated learning. The preparation of planning documents used by teachers is also still not optimal in terms of formulating objectives, the existence of prerequisite knowledge components, diagnostic assessments, triggering questions, differentiated learning planning, and numerical activities. Strengthening teachers is needed to improve the shortcomings in the implementation of the Pancasila learner profile in the Biology learning process. Key words: Pancasila student profile, biology learning, Merdeka Curriculum Â ABSTRAK Tujuan penelitian ini adalah untuk menganalisis profil pancasila dalam pembelajaran biologi. Penelitian ini merupakan penelitian kualitatif deskriptif, dengan sampel penelitian enam SMA pengimplementasi Kurikulum Merdeka kategori mandiri belajar. diambil secara proposional antara sekolah negeri dan swasta. Informan penelitian ini adalah guru Biologi kelas X. Pengumpulan data dilakukan dengan menggunakan angket, wawancara, dan dokumentasi. Analisis data kualitatif dilakukan dengan aktivitas data reduction, data display, dan conclusion drawing. Hasil penelitian menunjukan implementasi penguatan profil pelajar Pancasila dalam proses pembelajaran biologi telah terlaksana dengan ditemukannya nilai-nilai dimensi profil pelajar Pancasila, yaitu dimensi bernalar kritis, berkakhlak mulia, gotong royong, dan kreatif. Nilai dimensi bernalar kritis menjadi yang paling dominan muncul.Â Namun masih ditemukan kekurangan dalam pelaksanaannya berkaitan dengan belum sepenuhnya guru menyesuaikan pembelajaran dengan kondisi peserta didik dan melakukan penilaian diagnostik untuk pembelajaran terdiferensiasi. Penyusunan dokumen perencanaan yang digunakan guru juga masih belum maksimal dalam hal perumusan tujuan, keberadaan komponen pengetahuan prasyarat, penilaian diagnostik, pertanyaan pemantik, perencanaan pembelajaran terdiferensiasi, dan kegiatan numerik. Penguatan terhadap guru diperlukan untuk menyempurnakan kekurangan dalam implementasi profil pelajar Pancasila pada proses pembelajaran Biologi. Kata kunci: Profil pelajar Pancasila, Pembelajaran Biologi, Kurikulum Merdeka